Self-instructional manual and pre-professional teaching performance of mathematics and physics students of the Universidad Nacional Hermilio Valdizan - Norberto Chávez, Liz Anaey; Anaya Huaranga, Cleycy; Paragua Morales, Melecio; Paragua Macuri, Carlos Alberto; Paragua Macuri, Melissa Gabriela (Escuela Profesional de Ciencias de la Comunicación Social de la Universidad Nacional del Altiplano, 2018)
The purpose of the research was to prove that the application of the self-instructional manual improves the pre-professional teaching performance of the students of the professional school of mathematics and physics of the national university Hermilio Valdizán, for which a research of type was developed explanatory and quasi-experimental design; the study population consisted of 84 students and a non-random sample was taken, with experimental group = 12 and control group = 14; the instrument used was a valued evaluation test, with the name of initial and final test, with ten indicators each test, whose valuation is from 1 to 4 for each indicator, which produced the following rating scale: [10 - 40] ; for the processing of the data, the descriptive statistics and inferential statistics were used, obtaining the following result and conclusion: in the dimension Planning of the pedagogical work, the test T value = 2.23; in the Management dimension of learning-teaching processes, the Test T value = 2.92; and, in the Professional Responsibility dimension, the Test T value = 2.80; in all three cases they were located to the right of t critic = 1.71; which is the rejection zone, therefore the null hypothesis was rejected and the alternative hypothesis was accepted; as a conclusion it was proved that the application of the self-instructional manual improves the teaching performance in the three dimensions in the students of the Professional School of Mathematics and Physics.